The Mediated Politics of Europe
XVII, 345 p. 20 illus.
Keywords: This edited collection makes a unique contribution to analyses of the changing nature and challenges of mediated political communication, through a distinctive comparative discourse analytical approach. The book explores how politics is performed and discursively constructed in television news and current affairs in five countries (France, Greece, Italy, Sweden and the UK) and focuses on a moment in time in European politics characterized by challenging tensions; increased Euroscepticism, questioning of mainstream politics; accentuated gaps between the elite and the citizens, and polarizations between member states. Emphasising the performative and discursive dimensions of political communication, the chapters provide a detailed comparative analysis that is centred around three themes: how symbolic representations of politics are shaped by journalistic practices, genres and styles of news reporting; the language and performances of mainstream and populist political leaders; and the participation and representation of citizens’ voices. .